PERTUMBUHAN PENJUALAN, MARJIN LABA BERSIH, DAN PENGEMBALIAN EKUITAS TERHADAP HARGA SAHAM : (STUDI PADA PERUSAHAAN SUB SEKTOR BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Dhemas Juliet Raihana Sudaryanta; Zain Zainuddin; Sat Yudha Dhahana (Desanta Publisher, 2026)
This research aims to examine and obtain empirical evidence of the influence of sales growth, net profit margin and return on equity on stock prices. The population in this study are coal sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used purposive sampling, resulting in 20 companies were obtained that met the criteria, with a total of 100 observations. The analytical methods used in this research are descriptive statistics, classical assumption tests, panel data, coefficient of determination, t-test, and F-test using the EViews 13 analysis tool. The research results show that sales growth has an effect on stock prices. Net profit margin affects share prices. Return on equity has no effect on share prices. Sales growth, net profit margin, and return on equity simultaneously influence stock prices